PERILAKU BULLYING DAN KARAKTER REMAJA SERTA KAITANNYA DENGAN KARAKTERISTIK KELUARGA DAN PEER GROUP - Karina, Karina; Hastuti, Dwi; Alfiasari, Alfiasari (Jurnal Ilmu Keluarga dan Konsumen, 2013)
The purpose of this study was to determine the relationship among family characteristic, peer group, character (respectful and empathy), and bullying of youth at Bogor City. This study also aim to analyse the difference of peer group cohesiveness, bullying role, and character based on sex and school group. Fifty female and fifty male students, ages 16-18, from public and private vocational high school were selected by cluster random sampling. Result showed that there was significant difference at peer group cohesiveness between private and public schools, but no difference between male and female students. Female students more respectful than male and it were significantly different. Based on school group, there was no difference on their character. Female students also had higher score of bullying and they dominantly conducted verbal bullying. Ages of parents was significantly related to character of youth (respectful and empathy). Peer group cohesiveness was significantly related to bullying; the more cohessive to their peers, more bullying conducted by youth. It also showed that character were negatively significant related with bullying.